Gall stone recurrence and its prevention: the British/Belgian Gall Stone Study Group's post-dissolution trial. Issue 9 (September 1993) - Hood, K A; Gleeson, D; Ruppin, D C; Dowling, R H
Abstract : The British/Belgian Gall Stone Study Group (BBGSG) post-dissolution trial was a prospective, multicentre, randomised, double blind trial of: (i) low dose ursodeoxycholic acid, (ii) placebo, and (iii) a high fibre, low refined carbohydrate diet in the prevention of gall stone recurrence in patients with complete gall stone dissolution. Further aims included establishing the timing and frequency of recurrence and its association with biliary symptoms, a comparison of the sensitivity of ultrasonography v oral cholecystectography in detecting recurrent stones, and a search for risk factors predicting recurrence. Ninety three patients entered the study, and 82 were followed up for up to five years (mean (SEM) 28 (1.5) months) with six monthly ultrasonography and yearly oral cholecystectography. There were 21 recurrences (26 by oral cholecystectography or ultrasonography, or both), only two of which were symptomatic, which were detected between 12 and 42 months after trial entry. This corresponded to an actuarial recurrence rate of 33.9 (7.0%) by lifetable analysis at 42 months and subsequently. There were four recurrences in the ursodeoxycholic acid, six in the placebo, and 11 in the diet groups, corresponding to 21.9 (9.9)%, 27.4 (10.1)%, and 45.8 (12.4)% respectively at 42 months by lifetable analysis (NS). Variables including age, obesity, menopausal state, pregnancy, and oestrogen containing drugs were not shown to affect recurrence rate. Men had more frequent recurrence than women (NS). Patients who had had multiple stones experienced more recurrences than did those with single stones (NS). Recurrence did not occur in patients who took non-steroidal anti-inflammatory drugs (NSAIDs) (p < 0.02). The stone free interval between stone dissolution and trial entry proved to be important--those stone free > nine months had a recurrence rate of only 12.7 (6.0)% at 42 months compared with 55.4 (12.5)% in those stone free < nine months (p < 0.01). There was imbalance between the ursodeoxycholic acid and placebo groups for this factor, and after applying a statistical correction, the adjusted recurrence rate in the ursodeoxycholic acid group was 15% compared with 30% in both placebo and diet groups (NS). These data suggest that after medical dissolution, the risk of gall stone recurrence is not reduced by a high fibre, low refined carbohydrate diet: it may be lowered, but not abolished, by low dose ursodeoxycholic acid.